Pengembangan Potensi Desa Salamrejo dan Proses Pembelajaran Efektif Bagi Anak Dan Orang Tua Selama Pandemi - Panglipurjati, Puspaningtyas (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2021)
Kuliah Kerja Nyata (KKN) is a course in the form of activities that combines the implementation of the three basic pillars (tri dharma) of higher education. The purpose of this KKN program is to provide knowledge to residents of Sentolo District, Salamrejo Village regarding the potential that exists in the village. The work programs implemented are village potential work programs and pocket book work programs which are implemented using a qualitative approach based on references in the form of journals obtained from the internet. The result of this work program is a proposal in developing the potential of villages in Salamrejo Village in the form of counseling related to the development of natural fiber crafts based on industrial classification and the development of tourist destinations which are carried out with several regional geographic approaches as well as a pocket book work program which is counseling related to tips or supporting factors. in order to create `` the effectiveness and efficiency of online learning during the pandemic period '' for children and parents by using the Internet.